Data for Financial market integration in sub-Saharan Africa: How important is contagion? - Ahmad Hassan Ahmad; Simeon Coleman; Robert Akunga (2022)
This is the data set used for "Financial market integration in sub-Saharan Africa: How important is contagion?" as described in the paper.